2016
DOI: 10.1016/j.jclepro.2015.09.115
|View full text |Cite
|
Sign up to set email alerts
|

Generic time- and method-interdependencies of empirical impact-measurements: A generalizable model of adaptation-processes of carsharing-users' mobility-behavior over time

Abstract: The purpose of this article is to advance empirical sustainability-evaluations of carsharing-systems. Carsharing, a frequently cited example of a product-service system (PSS), is currently morphing from a niche into a mainstream mode of transportation. Carsharing has the potential to provide a more sustainable mobility-option compared to private car usage, for example by reducing the overall motor-vehicle traffic in cities. However, the quantification of this potential is complex, and few studies have analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 67 publications
1
2
0
Order By: Relevance
“…The study involved all three categories of PSS, investigating for example reuse and recycle in the case of product-oriented PSS (which can be considered the main elements behind circular economy concept), and collaborative consumption and sharing models in the case of use-oriented PSS. Indeed this example shows a renewed interest in business models and sustainability, as evidenced also by other recent works (Emili et al, 2016;Firnkorn and Shaheen, 2016;Pereira et al, 2016) Furthermore, from the analysis of main topics (Table 5), we found a very small number of publications dealing with the topic of economic analysis of PSS and with social/environmental analysis.…”
Section: Future Research Directionssupporting
confidence: 73%
“…The study involved all three categories of PSS, investigating for example reuse and recycle in the case of product-oriented PSS (which can be considered the main elements behind circular economy concept), and collaborative consumption and sharing models in the case of use-oriented PSS. Indeed this example shows a renewed interest in business models and sustainability, as evidenced also by other recent works (Emili et al, 2016;Firnkorn and Shaheen, 2016;Pereira et al, 2016) Furthermore, from the analysis of main topics (Table 5), we found a very small number of publications dealing with the topic of economic analysis of PSS and with social/environmental analysis.…”
Section: Future Research Directionssupporting
confidence: 73%
“…This result could indicate a low perception of carsharing as a way of reducing environmental impact (since it is car-based). Despite the forecasted reduction in CO2 emissions and land use due to the use of carsharing instead of private cars [72], the impact assessment of the carsharing is complex, and it depends on the time framings of methodological designs (if it is cross-sectional, 'before-after' or longitudinal designs) [73]. Additionally, other factors can be more relevant to the decision to use carsharing, and concerns toward the environment are not always aligned with pro-environmental behavior performance [74].…”
Section: Discussionmentioning
confidence: 99%
“…In 2015, China presented the biggest fleet in the world with 753,508 bicycles, followed by France with 42,930, and Spain with 25,084 ( 4 ). Categorization of bike sharing systems can be defined by the use of stations or not: (a) station-based (SBBS), b) free-floating (FFBS), and c) a mix of the two ( 5 ).…”
mentioning
confidence: 99%